Validity and sensitivity of a submaximal fitness test for assessing cardiorespiratory fitness and response to preseason training load in female football players - MacKenzie, L; Lovell, R; Atkinson, L; Naumovski, D; Shushan, T. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To evaluate the within-athlete sensitivity, validity, and dose-response relationships of exercise heart rate (HRex) from a submaximal fitness test (SMFT) as a proxy measure of cardiorespiratory fitness.